Changing incidence of oral and maxillofacial tumours in East Java, Indonesia, 1987-1992. Part 2: Malignant tumours - Budhy, T.I.; Soenarto, S.D.; Yaacob, H.B.; Ngeow, Wei Cheong (Elsevier, 2001)
A total of 2193 tumours of the mouth and jaw diagnosed at the Laboratorium Patologi Anatomi Fakultas Kedokteran Universitas Airlangga, Indonesia from 1987 to 1992, inclusive, was studied. Malignant tumours constituted 45.3 of the lesions. Almost 71 of the malignant tumours were squamous cell carcinomas. The remainder were salivary gland tumours (21.5) and sarcomas (4.5). The male to female ratio for malignant tumours was 5.1:4.7. The incidence of malignant tumours per 100,000 population over the 6-year study period was 2.64. The yearly incidence seemed to increase except in 1990, when it dropped. The incidence of squamous cell carcinoma over the 6 years was 2.1. Calculation of the odds ratio suggested that people aged 40 and over are 5.8 times more likely to develop squamous cell carcinoma. Copyright 2001 The British Association of Oral and Maxillofacial Surgeons.